The Reliability and Cross-Cultured Adaptation of the Boston Questionnaire; in Turkish Illiterate Patients - Pelin Yazgan; Zeynep Şimşek; İsmihan Orhan and Lyold Beachy and Yaşar Özkul and Mehmet Ali Kurcer (Archives of Rheumatology, 2009)
Objective: In Turkey, the illiterate patients may not be able to complete many self-administered questionnaires. The aim of this study was to adapt the self-administered Boston questionnaire (BQ) for the assessment of the severity of symptoms and functional status (BQ-SS, BQ-F) in carpal tunnel syndrome to the illiterate Turkish population and investigate the reliability of the cross cultured adaptation. Material and Methods: A total of 120 outpatients with carpal tunnel syndrome (60 literate, 60 illiterate) were assessed using this Turkish version of BQ. Translation/back-translation of the English version BQ was done by using blinded method and independently by four different individuals, and adapted by a team. For illiterate people, the term “writing” was changed as “crocheting” and the statement “holding a book while reading” was modified as “holding the Holy Quran while reading”. Reliability was investigated by the reproducibility and internal consistency. Results: Cronbach’s alpha was calculated at 0.914 for BQ-SS scale, 0.94 for BQ-F scale in the illiterate group and at 0.971 for BQ-SS scale, 0.96 for BQ-F scale in the literate group, respectively. The intraclass correlation coefficients were excellent and range between 0.89 and 0.96 for BQ-SS and BQ-F in the illiterate and the literate patients. Conclusion: This adapted version of BQ provides a reliable tool in iliterate Turkish patients with carpal tunnel syndrome. For application of self-administered questionnaire, some conceptual modifications should be required for accommodation of the different educational levels. (Turk J Rheumatol 2009; 24: 10-6)